Water, neighborhoods and urban design: Micro-utilities and the fifth infrastructure - Vicki Elmer; H. Fraker (University of California, Institute of Urban and Regional Development (IURD), 2011)
The eco-city rejects the idea of waste, instead seeking to transform it into beneficial uses within the city. In so doing, it seeks to reduce inputs of water and energy from afar. This concept is behind efforts to decentralize the production of energy and food and to create more local 'green' employment. It also powers the three 'Rs' of solid waste management as well as transportation efforts such as transit oriented development, walkable neighbourhoods, and 'complete streets'. Architects, planners and landscape architects have used many of these innovations at the building site level over the past twenty years. The next breakthrough is to integrate these systems at the neighbourhood, block or development cluster to begin to approach zero emissions. This paper begins by describing energy and water innovations at the site and building level before examining the experiences of six cities that have tried to integrate water, energy and solid waste utilities in new neighbourhoods. In so doing, these pioneers have begun to move towards the development of micro-utilities that use the landscape as the fifth infrastructure for true sustainability.
Keywords: 330